Deep Vein Thrombus Occurring Immediately After Blunt Abdominal Trauma - Oshima, Kiyohiro; Hagiwara, Shuichi; Murata, Masato; Aoki, Makoto; Kaneko, Minoru; Niwamae, Nogiku; Kurabayashi, Masahiko (Pediatric emergency care, 2016)
A 13-year-old adolescent girl with blunt abdominal injury was transferred to our hospital. Enhanced computed tomography (CT) showed not only retroperitoneal hematoma around the inferior vena cava and left common iliac vein but also thrombus extending from the left common iliac vein to the femoral vein. Enhanced CT performed on the second day revealed no increase in retroperitoneal hematoma and a new small thrombus in the popliteal vein. Anticoagulant therapy was therefore started with administration of unfractionated heparin. Administration of warfarin was started on the 12th day and heparin administration was stopped on the 14th day. The patient was discharged on the 19th day with continuation of warfarin administration. Enhanced CT performed 10 months after injury showed no thrombus, and the administration of warfarin was then stopped. She was successfully treated with the appropriate start time and control of anticoagulation therapy based on careful evaluation of her general condition.